Subjects and Aliens - Bagnall, Kate; Prince, Peter (ANU Press, 2024)
Subjects and Aliens confronts the problematic history of belonging in Australia and New Zealand. In both countries, race has often been more important than the law in determining who is considered 'one of us'. Each chapter in the collection highlights the lived experiences of people who negotiated laws and policies relating to nationality and citizenship rights in twentieth-century Australasia, including Chinese Australians enlisting during the First World War, Dalmatian gum-diggers turned farmers in New Zealand, Indians in 1920s Australia arguing for their citizenship rights, and Australian women who lost their nationality after marrying non-British subjects. The book also considers how the legal belonging—and accompanying rights and protections—of First Nations people has been denied, despite the High Court of Australia’s recent assertion (in the landmark Love & Thoms case of 2020) that Aboriginal people have never been considered ‘aliens’ or ‘foreigners’ since 1788. The experiences of world-famous artist Albert Namatjira, and of those made to apply for ‘certificates of citizenship’ under Western Australian law, suggest otherwise. Subjects and Aliens demonstrates how people who legally belonged were denied rights and protections as citizens through the actions of those who created, administered and interpreted the law across the twentieth century, and how the legal ramifications of those actions can still be felt today.